Proto-ALGIC IV: Nouns - Proulx, Paul (Kansas Working Papers in Linguistics, 1992)
In Proto-Algic, a primary noun stem often ends in a derivational final, a secondary one in a nominalizer. Both usually resemble demonstrative pronouns in shape. A dependent noun stem lacks a root, and generally begins in **i:, **o:, or in a consonant other than **2 or **k(w). In those cases where it is paired with a medial beginning in **2 or **k(w), a prefix receptor (**-c, **–I, **-s, **-S, or **-t) is prefixed. Inflection for allocation differs for kin, human body parts, parts of nonhumans, and general nouns.